2019
DOI: 10.1108/jabs-07-2019-0214
|View full text |Cite
|
Sign up to set email alerts
|

The dynamic impact of board composition on CSR practices and their mutual effect on organizational returns

Abstract: Purpose The purpose of this paper is twofold. First, it aims to investigate the dynamic impact of board composition (board size, board independence and board diversity) on independent corporate social responsibility (CSR) practices (marketplace, environment, community and workplace). Second, it tends to examine the mutual effect of board composition and CSR practices on organizational returns (return on assets and Tobin’s Q) of 631 Malaysian PLCs listed on Bursa Malaysia during 2006-2017. Design/methodology/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
55
0
8

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 74 publications
(154 reference statements)
4
55
0
8
Order By: Relevance
“…Alazzani et al [103] reported that while board gender diversity gives rise to improved social action by firms, the same is not true in relation to the environment. Such findings have been corroborated by studies that exclusively examine environmental performance [97,106].…”
Section: Board Gender Diversity and Environmental Performancementioning
confidence: 60%
See 3 more Smart Citations
“…Alazzani et al [103] reported that while board gender diversity gives rise to improved social action by firms, the same is not true in relation to the environment. Such findings have been corroborated by studies that exclusively examine environmental performance [97,106].…”
Section: Board Gender Diversity and Environmental Performancementioning
confidence: 60%
“…The results for the relationship of interest are also shown. [27,47,85,89] Use of resources [27,71,85] Emissions [19,47,72,85,[90][91][92] Environmental innovation [30,31,93,94] Environmental performance Negative relationship [87] Consumption of water and energy [95] Environmental innovation [28,34,[96][97][98][99][100][101][102][103][104][105][106] Environmental performance No relationship [29] Consumption of energy [27,85] Environmental innovation Source: authors, based on the literature review.…”
Section: Board Gender Diversity and Environmental Performancementioning
confidence: 99%
See 2 more Smart Citations
“…Though the board delegates both management functions and decision control functions to internal managers, they retain final control over the managers through the right to ratify key operational decisions (Duru et al, 2016). As Coles et al (2008) contend, complex firms should have higher board independence for better advice to the firm's CEO (Karim et al, 2019b;Sheikh & Karim, 2015).…”
Section: Interaction Effect Of Board Independencementioning
confidence: 99%